ALDH1A1 Genetic Variations May Modulate Risk of Parkinson’s Disease in Han Chinese Population - Fan, Hui-Hui; Guo, Qing; Zheng, Jing; Lian, Yi-Zhi; Huang, Shi-Shi; Sun, Yue; Zou, Ming; Zhu, Jian-Hong; Zhang, Xiong (Frontiers in Neuroscience, 2021)
Background: Studies in animal models have suggested that aldehyde dehydrogenase 1 (encoded by ALDH1A1) protects against Parkinson’s disease (PD) by reducing toxic metabolites of dopamine. Herein we aimed to investigate whether ALDH1A1 was genetically associated with PD susceptibility in humans. Methods: A Han Chinese population of 1039 subjects was recruited to analyze six tag-single nucleotide polymorphisms (SNPs), followed by haplotype analyses and variants interaction analyses. Real-time PCR was used to analyze mRNA levels of ALDH1A1 in peripheral blood of 42 subjects. Results: The tag-SNP rs7043217 of ALDH1A1 was significantly associated with PD susceptibility with the T serving as a risk allele (genotype frequency, P = 0.030; allele frequency, P = 0.013, OR = 1.258, 95% CI =1.050-1.508). Multiple haplotypes were linked to abnormalities of PD risk, topped by a 4-SNP GGTA module in the order of rs4646547, rs1888202, rs7043217 and rs647880 (P = 9.610 × 10-8, OR = 6.420, 95% CI = 2.944-13.998). Interaction analyses showed that a simultaneous presence of the CC genotype of rs7043217 and the TT genotype of ALDH2 variant rs4767944 conferred an elevated protection against PD (P = 4.68×10-4, OR = 0.378, 95% CI = 0.219-0.652). The mRNA expression of ALDH1A1 showed a trend of reduction (P = 0.084) in PD patients compared to the controls. Conclusion: Our results provide novel genetic insights into the role of ALDH1 in PD pathogenesis.